Molecular Detection and Characterization of Haemonchus spp. in Cattle in Nigeria - Olamilekan Banwo; Olalekan Jeremiah; Rofiat Adesina; Abraham Adeyemo; Olusegun Fagbohun (Iranian Journal of Parasitology)
Background: Haemonchosis is a major parasitic infestation in ruminant livestock, causing significant economic losses annually. The causative organisms are helminths of the genus Haemonchus spp. Detection of the causative agent is important for effective management and control of the disease. Molecular detection and characterization of parasites is a very dependable approach for parasite identification, especially where morphological characterization is unreliable.